A Theory of Assembly : From Museums to Memes - Parry, Kyle, 1985- (Book collections on Project MUSE., 2023)
"A vital reckoning with how we understand the basic categories of cultural expression in the digital era Digital and social media have transformed how much and how fast we communicate. But they have also altered the palette of expressive strategies: the cultural forms that shape how citizens, activists, and artists speak and interact. Most familiar among these strategies are storytelling and representation. In A Theory of Assembly, Kyle Parry argues that one of the most powerful and pervasive cultural forms in the digital era is assembly.Whether as subtle photographic sequences, satirical Venn diagrams, or networked archives, projects based in assembly do not so much narrate or represent the world as rearrange it. This work of rearranging can take place at any scale, from a simple pairing of images, undertaken by one person, to the whole history of internet memes, undertaken by millions. With examples ranging from GIFs and paintings to museum exhibitions and social movement hashtags, Parry shows how, in the internet age, assembly has come to equal narrative and representation in its reach and influence, particularly as a response to ecological and social violence. He also emphasizes the ambivalence of assembly-the way it can be both emancipatory and antidemocratic. As the world becomes ever hotter, more connected, and more algorithmic, the need to map-and remake-assembly's powers and perils becomes all the more pressing. Interdisciplinary, engaging, and experimental, A Theory of Assembly serves as a playbook of strategies and critical frameworks for artists, activists, and content creators committed to social and environmental justice, ultimately arguing for a collective reenvisioning of what cultural forms matter. "--